Effect of magnesium-mica during grazing and/or feedlot phases on performance of steers - Coffey, K.P.; Brazle, F.K.; Lomas, Lyle W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy-two mixed breed steers (679 lb avg BW) grazing smooth bromegrass pastures for 112 days were fed 2.2 lb/day of either a control supplement (PC) or one containing .075 lb/day of magnesium-mica (PMM). Following the grazing period, steers were placed in a feedlot with pasture groups split such that two of the groups fed each pasture supplement were fed a control supplement (FC) and two groups were fed a supplement containing 10% magnesium-mica (FMM). Steers fed PMM tended to gain faster than those fed PC during the pasture phase (2.41 vs. 2.32 lb/day). Steers fed PMM had higher dressing percentage (P<.05) and net carcass values (P<.06 ). Percent grading Choice was 41.7 for PMM vs. 27.8 for PC, and that difference also was reflected in marbling scores. No differential effect of feedlot supplement was detected for carcass measurements. Magnesium-mica fed during a pasture phase may affect subsequent marbling scores.
Keywords: Beef; Magnesium-mica; Smooth bromegrass; Feedlot; Marbling score